The crumbling or strengthening of social capital? - Iglič, Hajdeja (Družboslovne razprave, 2014)
The economic crisis is bringing uncertainty, change, worries and distress into the everyday lives of people, which has an effect on the level and form of social capital. The literature offers two opposing arguments regarding the impact of shocks and material uncertainty on social capital. The first one emphasises the instrumental nature of interpersonal relations and claims that the increased need for mutual help and support that arises during crisis periods strengthens social networks. In contrast, the second argument brings forward the problem of a social networks overload, which threatens to break them up during crises. More importantly, interpersonal dependence can lead to the closing off of social responsibility and solidarity into narrow family networks, thus reducing social capital among social groups and in society in general. In this paper, we empirically confront these two arguments in the context of the economic crisis of 2008 in Slovenia. We compare the characteristics of social networks and interpersonal trust before the crisis with those measured several years after it began.
Keywords: Social capital (Sociology); Socialni kapital (Sociologija); Social networks; Družbena omrežja; Trust; Zaupanje; Economic crises; Ekonomske krize; država blaginje